Assessment of the Relationship between Neighborhood Characteristics and Dental Caries Severity among Low-Income African-Americans: A Multilevel Approach - Marisol Tellez, BDS, MPH, PhD; Woosung Sohn, DDS, DrPH, PhD; Brian A. Burt, BDS, MPH, PhD; (Blackwell Synergy, 2006)
To assess the relationship between neighborhood effects and the severity of dental caries among low-income African-Americans.